Beginning PHP and MySQL - Gilmore, W. Jason (Springer, 2017)
Beginning PHP and MySQL: From Novice to Professional, Third Edition offers a comprehensive introduction to two of the most prominent open-source technologies on the planet: the PHP scripting language and the MySQL database server. Updated to introduce the features found in MySQL's most significant release to date, readers will learn how to take advantage of the features of both technologies to build powerful, manageable, and stable web applications.